Plan de negocios creación de una empresa exportadora de frutos deshidratados a la ciudad de Ámsterdam (2019)
The purpose of this degree work is to demonstrate the technical-financial viability of a business plan for the creation of a dehydrated fruit marketing company, for export to the city of Amsterdam. The feasibility studies of the project were carried out with the objective of determining the acceptance and distribution possibilities of the product in the city of Amsterdam, observing the advantages and disadvantages of its commercialization, the required investments and the risks when carrying out this business plan, in order to find real results to validate this proposal.